Characterization of LTE transmitter - Pandey, Vandana (2019)
In Cellular industry when it comes for a technology that is designed primarily for data, the Long Term Evolution (LTE) comes at first place and it is evolved from the Global System for Mobile communications (GSM) and Universal Mobile telecommunication System (UMTS) telecom standards which can also be referred as 2G and 3G standards respectively. LTE term was first coined as a part of 3GPP release 8 which was further enhanced in 3GPP release 9 and this enhancement continuous to improve in further releases. LTE uses a combination of different bandwidths of up to 20MHz and MIMO technology to offer theoretical data rates up to 300 Mbps. LTE has become so significant because it uses OFDM which is a multicarrier technique that exploits wider channel bandwidths more effectively. The objective of my master dissertation is an on-bench characterization of silicon LTE transmitter integrated circuit and to verify its front-end design specification. A detailed study and conceptual understanding are achieved in the process of characterizing the LTE transmitter IC developed for radio communication application. The RFICs are tested for a range of temperature against the various 3GPP specifications defined for LTE transmitter. To validate RFIC, a test program is written in MATLAB for each of the RF parameter to be tested. Test measurement instruments are remotely controlled using standard commands for programmable instruments (SCPI). The test program automation involves remotely tuning the magnitude and phase of an input RF signal to the desired level by controlling signal generators using SCPI commands. The thesis is concluded with the results obtained for signaling/non-signaling test and future scope in the improvement of results.